Character Education Based on National Values: A Case Study at Sekolah Kebangsaan Dato' Wan Ahmad Rasyid, Malaysia - Lukman Ismail; Sam'un Mukramin; Rinaldi Rinaldi; Sahabuddin Nanda; Norhayati binti Mohamed (Jurnal Pemberdayaan Masyarakat, 2026)
Character education based on national values is an important foundation for developing a generation that is not only knowledgeable but also possesses moral integrity and a love for the homeland. This study aims to analyze the implementation strategy for character education grounded in national values in schools, emphasizing the roles of the curriculum, extracurricular activities, school culture, teacher role models, and parental involvement. This research uses a descriptive qualitative approach with literature analysis and empirical studies at Sekolah Kebangsaan Dato' Wan Ahmad Rasyid. The results show that internalization of national values can be achieved systematically through integration into core subjects, reinforcement through extracurricular activities, and instilling these values in the school culture. Furthermore, teachers serve as primary role models in demonstrating national-spirited behavior, while collaboration with parents ensures the sustainability of character education beyond school. Thus, the implementation strategy for character education based on national values is holistic and multi-layered, strengthening students' national identity while acting as a bulwark against the influence of globalization.